Can we respect the principles of oncologic resection in an emergency surgery to treat colon cancer? - Teixeira, Frederico (BioMed Central, 2015)
Patients with colorectal cancer admitted to the emergency room are generally at more advanced stage of the disease and are usually submitted to a resection with curative intent in a smaller scale. In such scenario, one of the aspects to be considered is whether the principles of oncologic resection are observed when those patients diagnosed with colon cancer are treated with surgery. We selected 87 patients with adenocarcinoma of colon and/or upper rectum submitted to an emergency surgical resection. The major variables reviewed retrospectively were: the extent of resection performed, the number of dissected regional lymph nodes and the overall survival rate. Intestinal obstruction was observed in 67 patients (77%) while perforation was found in 20 patients (23%). Seven (8%) specimens had circumferential compromised margins, all found in patients with T4 tumors combine with poor clinical status. The number of dissected regional lymph nodes was greater than, or equal to, 12 in 71% of patients. While the average days of stay in the ICU was 5.7 days, the median was 3 days. The morbidity and peri-operative mortality stood at 33.6% and 20%, respectively. The outcome of an emergency surgery of colorectal cancer observed in this study was similar to those found in the literature. The principles of oncologic resection were respected when considering and analyzing the extent of the resection, the surgical margins and the number of dissected lymph nodes.